Risky health behaviors among students in Majmaah University, Kingdom of Saudi Arabia - Tahir Ansari; Talal Alghamdi; Mansour Alzahrani; Fahad Alfhaid; Waqas Sami; Bader A Aldahash; Dukhayel S Aldukhayel; Fahad S Alshanbah; Naif M Almutairi (Journal of Family and Community Medicine, 2016)
Introduction: Risky behaviors are those that potentially expose people to harm, or significant risk of harm, which prevent them from reaching their potential in life and which can cause significant morbidity or mortality. Objectives: The objectives of the study were to determine the overall prevalence of risky behaviors among university students; to determine the prevalence of smoking, drifting, fast driving and physical inactivity among university students; and to determine the associations between such behavior and demographic characteristics. Materials and Methods: An observational cross-sectional study conducted in three colleges. The data were randomly collected from 340 students aged 18-30 years from February to March 2015 using a self-administered questionnaire in Arabic. The data were entered using SPSS v 22.0. Mean and standard deviation were calculated for quantitative variables, and frequency and percentages were computed for categorical variables. Chi-square or Fisher′s Exact test, as appropriate, were used to test for statistical significance. Results: The overall prevalence of risky behaviors (smoking, drifting, fast driving, and physical inactivity) among students was 47.35%. Overall, 28% of the students were smokers, 25.2% were involved in drifting, 60.9% reported driving fast, and 66.4% were physically inactive. The age between 18-20 years was significantly associated with higher rates of drifting, fast driving, and physical inactivity. Conclusion: The prevalence of risky behaviors among university students was high. Physical inactivity and fast driving were the most common identified risky behaviors. Increasing awareness of these risks in the youth may significantly decrease related morbidities, complications, and even mortalities.